Land Use Land Cover Changes Detection of Erbil City Using GIS and Remote Sensing - Mohammed G. Mohammed (Polytechnic Journal)
Erbil City, the capital of the Kurdistan region in Iraq, witnessed significant land use land cover changes over the last two decades. These Land Cover Land Use (LULC) changes were attributed to many main social, political, climactic, and economic variables, especially after 2003 in Iraq. The use of geographic information systems and remote sensing became active tools that use public satellite images to detect LULC changes in cities. Two images of the study area of Erbil City for the years 2003 and 2020 respectively were used to analyze and get the nature and the magnitude of the LULC changes. Six LULC classes were recognized and compared for the sake of the analysis process. The LULC included barren, croplands, grasslands, open shrublands, savannas, and urban and built-up lands. Ground truth points were randomly projected and used to compare and validate the LULC class types. A confusion matrix was calculated based on the ground truth points comparison to assess the accuracy of the classes and to get the overall accuracy for the classified LULC. The LULC changes, magnitudes, and a table of “FROM-TO” changes were obtained. The maximum decrease change rate occurred in open shrublands with an average of ~ (-47%), however, the increase change rate in croplands was ~ (+17%), and for urbanizing areas was ~ (+11%). The barren and Savanna lands were proportionally small areas compared to other classes. The results showed that the overall accuracy was 90%, and the Kappa Coefficient value was 0.878.